Dapagliflozin and Cardiac, Kidney, and Limb Outcomes in Patients With and Without Peripheral Artery Disease in DECLARE-TIMI 58. Issue 8 (25th August 2020) - Bonaca, Marc P.; Wiviott, Stephen D.; Zelniker, Thomas A.; Mosenzon, Ofri; Bhatt, Deepak L.; Leiter, Lawrence A.; McGuire, Darren K.; Goodrich, Erica L.; De Mendonca Furtado, Remo Holanda; Wilding, John P.H.; Cahn, Avivit; Gause-Nilsson, Ingrid A.M.; et al.
Abstract : Background: Patients with peripheral artery disease (PAD) are at heightened risk of cardiovascular complications. The sodium-glucose cotransporter 2 inhibitor dapagliflozin reduces the risk for hospitalization for heart failure (HHF) and kidney events in patients with type 2 diabetes mellitus. An increased risk of amputation has been observed with canagliflozin in 1 previous trial. We examined cardiovascular and kidney efficacy and the risk of limb-related events in patients with and without PAD in an exploratory analysis. Methods: A total of 17 160 patients with type 2 diabetes mellitus, including 1025 (6%) with PAD, were randomized. Key efficacy outcomes were MACE (cardiovascular [CV] death, myocardial infarction, stroke), CV death/HHF, and progression of kidney disease. Amputations, peripheral revascularization, and limb ischemic adverse events were site-reported and categorized by a blinded reviewer. Results: Patients in the placebo arm with PAD versus those without tended to have higher adjusted risk of CV death, myocardial infarction, or stroke (adjusted hazard ratio [HR], 1.23 [95% CI, 0.97–1.56], P =0.094) and significantly higher adjusted risk of CV death/HHF (adjusted HR, 1.60 [95% CI, 1.21–2.12], P =0.0010) and progression of kidney disease (adjusted HR, 1.51 [95% CI, 1.13 – 2.03], P =0.0058), and limb adverse events (adjusted HR, 8.37, P <0.001). The relative risk reductions with dapagliflozin for CV death/HHF (HR, 0.86, PAD; HR, 0.82, no-PAD; P -interaction=0.79) and progression of kidney disease (HR, 0.78, PAD; HR, 0.76, no-PAD; P -interaction=0.84) were consistent regardless of PAD. There were 560 patients who had at least 1 limb ischemic event, 454 patients with at least 1 peripheral revascularization, and 236 patients with at least 1 amputation, with a total of 407 amputations reported. Overall, there were no significant differences in any limb outcome with dapagliflozin versus placebo including limb ischemic adverse events (HR, 1.07 [95% CI, 0.90–1.26]) and amputation (HR, 1.09 [95% CI, 0.84–1.40]), with no significant interactions by a history of PAD versus not ( P -interactions=0.30 and 0.093, respectively). Conclusions: Patients with versus without PAD are at a higher risk of CV death of CV death, HHF, and kidney outcomes, and have a consistent benefits for CV death/HHF and progression of kidney disease with dapagliflozin. Patients with PAD had a higher risk of limb events, with no consistent pattern of incremental risk observed with dapagliflozin. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01730534. Abstract : Supplemental Digital Content is available in the text.